A Decision Support System for Decongesting Prison in Edo State - GODFREY OISE (RADINKA JAYA UTAMA PUBLISHER, 2023)
Three prisons in Edo state-Okho, Ozalla Farm, and Ubiaja-are used as case studies in this study, which focuses on the challenges of decongesting the country's jail system. The study's objective was to develop a decision support system (DSS) to aid in ranking and recommending inmates based on an acquittal likelihood factor who should be fast-tracked for a speedy trial, bail, or relocation/recommendation for other correctional techniques or facilities within the Nigerian legal system; aside from the prison. The paper presents a model for a decision support system that incorporates three multi-criteria decision-making systems, SAW, TOPSIS, and AHP, as well as six factors: those who are awaiting trial, detained, sentenced to life, condemned inmates, long-term offenders, and those who have received only a light sentence. While assigning weights to rank the prisoners, consider their dependency, age, gender, health status, and percentage of their sentence served. Experts, including two magistrates, ten prison wardens, five attorneys, ten convicts, six pastors, and nine NGO employees, engaged in a questionnaire poll to predetermine weights. The DSS offers the decision maker two different levels of guidance, namely (a) a beginner mode and (b) an expert mode. The beginner mode is intended for decision-makers who are not familiar with the multi-criteria process. The advanced mode is employed when the decision-maker is conversant with the MA method and can choose a particular method using the predefined weights.